Content Based Authentication of Visual Cryptography - Wang, G; Yan, Wei Qi; Kankanhalli, M (Springer, 2016)
Visual Cryptography (VC) has been developed as a significant research arena in media security. Despite of its obvious strengths, recent investigations have debated this scheme from adverse aspects, its problem is lack of authentication of VC shares, VC authentication related to digital image processing and cryptography has not been fully integrated together in the past years. In this paper, we analyze both visual features and cryptographic features of VC shares and take use of them for VC authentication. Compared to those existing methods, our contribution is the first one to integrate visual features and cryptographic features of VC shares into Hash code for the purpose of VC authentication.
Keywords: Visual cryptography; Secret sharing; Digital image processing